PROGRAM PENDAMPINGAN BELAJAR BAGI ANAK TUNANETRA DI YAYASAN KESEJAHTERAAN TUNANETRA ISLAM - Fadliyaturrohmah (CV. Amerta Media, 2018)
Every child has the right to get a proper education, as well as a blind child. Learning is a primary requirement for all learners. With the fulfillment of the child's learning needs, then the welfare of children in education can be realized Learning assistance program encourages children to have competencies that enable children to achieve welfare. With the achievement of learning competencies, they can be fulfilled academic needs, psychological and social. Competence owned by the child so as to achieve the welfare of the outcomes of learning advisory program is done as a Competence in collecting, sorting, processing and managing information as well as competence in mastering the equipment as a means to know and understand. Competence in communicating with others effectively and competence to adapt to life changesKey Words: Learning Assistance Program, Blind Children, Yaketunis